Blockchain-CIM Governance Framework for Smart Cities: Simulation, Prototype, and Cross-Regional Validation - Abdullah Mohammed Almahdi; Mohsen Ibrahim Mohamed (African Journal of Advanced Pure and Applied Sciences, 2026)
Urban data ecosystems in contemporary smart cities face significant challenges due to heterogeneous, high-velocity data streams. The integration of blockchain distributed ledger technology (DLT) with City Information Modelling (CIM) platforms presents a trilemma: cryptographically verifiable data transparency, heterogeneous format interoperability, and regulatory data sovereignty. Despite extensive conceptual literature, the scalability-interoperability-governance trade-off has not been quantitatively assessed within a single, methodologically transparent framework featuring explicit production calibration and prototype validation. This study aims to develop, implement, and validate the Blockchain-CIM Governance Framework (BCGF), a six-construct governance model rooted in Institutional Theory, Technology Acceptance Model, and Resource-Based View. Validation was conducted through three complementary instruments: a production-calibrated Python simulation (5,000 transactions), a functional prototype deployed on a three-organization Hyperledger Fabric v2.5 testbed, and a stratified cross-sectional survey of 214 urban data governance professionals across five geographic regions. Findings indicate that inline format conversion imposes a statistically significant latency overhead of 16-32%, with IFC-to-canonical conversion incurring the highest cost (+28.4% in simulation; +32.1% in prototype). A batch size of 25-50 KB achieved production-equivalent throughput (850-3,000 TPS) with sub-500 ms latency. Audit-trail immutability positively correlated with stakeholder trust across all five geographic regions (beta = 0.52, R2 = 0.73). Raft consensus imposed a +12-18% energy overhead compared to PBFT’s +34-68%. The IPFS hybrid architecture achieved >= 99.84% on-chain storage reduction while satisfying GDPR Article 17 erasure requirements. This research contributes the BCGF as the first CFA-validated six-construct governance framework for blockchain-CIM integration, a quantified inline format conversion overhead, three novel validated instruments, a comprehensive regional survey, an energy-efficient consensus decision framework, a GDPR-compliant architecture, and a functional prototype implementation.